Settlement Of Stock Price Issues With Dividend Payout Ratio And Debt To Asset Ratio As Moderating Variables In The Retail Sub Sector - Denny Kurnia; Deni Sunaryo (Universitas Serang Raya, 2023)
This study aims to examine the effect of Net Profit Margin (NPM), Quick Margin (QR), and Receivable Turnover Ratio (RT) on stock prices moderated by Dividend Payout Ratio and Debt to Asset Ratio. This study uses the research object of retail sub-sector companies in Southeast Asia for the period 2012-2020. The data collected is secondary data with the documentation method in the form of the company's annual report. In this study, the sampling used nonprobability sampling technique with purposive sampling type, in which there are 10 companies in Southeast Asia that have complete financial statements according to the variables studied so that 72 research samples are obtained. The research method uses descriptive analysis, classical assumption test, measurement with autocorrelation. Multiple regression analysis, moderated regression analysis, adjusted R2. The results of this study are that NPM and RCT have no significant and partial effect on stock prices, while QR has a partial and significant effect on stock prices. The F test shows the results that NPM, QR, and RCT have a simultaneous effect on stock prices. In the results of the DPR MRA test, it can moderate the effect of NPM, QR, and RCT on stock prices, while DAR can only moderate the effect of RCT on stock prices.